Exploring Familiarity and Challenges in Environmental Impact Assessment Implementation for Major Highway Projects - Vikas Patidar (Mathematical Statistician and Engineering Applications, 2022)
Even though they are essential for improving transportation infrastructure, highway construction projects can have major effects on the environment. The efficient execution of Environmental Impact Assessments (EIAs) is of utmost importance in today's world of sustainable development, where societal and economic advancement go hand in hand. Through a survey of local practitioners, this study discovers how well-known EIA is for large-scale highway projects in Tamil Nadu, as well as the most typical obstacles to its implementation. According to the findings, the problem is with the way the EIA process is separated from the different phases of the project. Additionally, it shows that there are issues related to practitioners' lack of competence and abilities and the restricted data availability that prevents them from doing the necessary evaluation for specific effect categories.